MENINGKATKAN KETERAMPILAN GURU DALAM MEMANFAATKAN SAMPAH MELALUI PENDAMPINGAN PEMBELAJARAN SENI BUDAYA DI SD NEGERI 060877 MEDAN PERJUANGAN - Apiek Gandamana; Adek Cerah Kurnia Azis; Peny Husna Handayani; Waliyul Maulana Siregar (Universitas Negeri Medan, 2021)
Abstract: This community service activity aims to improve the skills of classroom teachers, especially the content of Cultural Arts and Crafts at SD Negeri 060877 Medan Perjuangan in utilizing waste into montage, collage and mosaic works. Elementary school students are important in learning cultural arts and crafts to practice multilingual, multidimensional and multicultural traits. Therefore, a classroom teacher must train skills in cultural arts and crafts. Therefore, community service has been carried out in the form of assistance to improve teachers' skills in utilizing waste. The method used in mentoring has stages of activities such as: preparation, implementation, evaluation and reflection and follow-up. The output of the assistance program includes: 1) A guidebook in the form of types and kinds of waste; 2) Practical manuals in making montage, collage, and mosaic works; 3) A tutorial guide for making montage, collage, and mosaic works; 4) Montage, collage and mosaic works; 5) Exhibition of montage, collage and mosaic works. Thus, community service activities in the form of assistance in utilizing waste can improve the skills of teachers at SD Negeri 060877 Medan Perjuangan.Key words: learning art and culture, montage, collage and mosaicAbstrak:Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan keterampilan guru kelas khususnya muatan Seni Budaya dan Prakarya di SD Negeri 060877 Medan Perjuangan dalam memanfaatkan sampah menjadi karya montase, kolase dan mozaik. Siswa Sekolah Dasar penting dalam pembelajaran seni budaya dan prakarya untuk melatih sifat multilingual, multidimensional, dan multikultural.Oleh sebab itu, seorang guru kelas harus melatih kemampuan dalam seni budaya dan prakarya.Maka dari itu, pengabdian kepada masyarakat telah terlaksana berupa pendampingan untuk meningkatkan keterampilan guru dalam memanfaatkan sampah. Metode yang dipakai dalam pendampingan memiliki tahapan kegiatan seperti: persiapan, pelaksanaan, evaluasi dan refleksi serta tindak lanjut. Luaran program pendampingan antara lain: 1) Buku panduan berupa jenis dan macam-macam sampah; 2) Buku panduan pratikum dalam membuat karya montase, kolase, dan mozaik; 3) Buku panduan tutorial pembuatan karya montase, kolase, dan mozaik; 4) Karya montase, kolase dan mozaik; 5) Pameran karya montase, kolase dan mozaik. Dengan demikian kegiatan pengabdian kepada masyarakat berupa pendampmgan dalam memanfaatkan sampah dapat meningkatkan keterampilan guru di SD Negeri 060877 Medan Perjuangan.Kata kunci: pembelajaran seni budaya dan prakarya, montase, kolase dan mozaik